Probabilistic risk assessment (PRA) on supercritical water cooled reactors (SCWRs) - Lin, Yan Jing (2015)
Nuclear energy is attracting more and more attention in recent decades because of its high efficiency. The supercritical water reactor (SCWR) is a theoretical concept of future nuclear reactors. It is designed based on the existing CANada Deuterium Uranium (CANDU). For nuclear power plants, safety concern is very important. In this project, the comparison between CANDU and SCWR design are made to highlight the advanced characteristics and safety guarantees of SCWR. Probabilistic risk assessment (PRA) is the main method involved to provide logical and numerical support of assessment result. Even though SCWR is currently in pre-conceptual phase, PRA can provide safety reference and suggest design improvement. Future study can also be conducted based on this safety analysis.